A Peroxiredoxin From the Haemaphysalis longicornis Tick Affects Langat Virus Replication in a Hamster Cell Line - Kusakisako, Kodai; Morokuma, Haruki; Talactac, Melbourne Rio; Hernandez, Emmanuel Pacia; Yoshii, Kentaro; Tanaka, Tetsuya (Frontiers in Cellular and Infection Microbiology, 2020)
Ticks are hematophagous arthropods, and their blood feeding on vertebrate hosts is essential for their development. The vertebrate blood contains high levels of free iron that can react with oxygen in ticks, resulting in the production of hydrogen peroxide (H2O2), one of the reactive oxygen species. Peroxiredoxins (Prxs), H2O2-scavenging enzymes, take on an important role in the ticks’ oxidative stress coping mechanism. Ticks also transmit several disease-causing pathogens, including tick-borne encephalitis virus (TBEV), in animals and humans. Therefore, the control of ticks and tick-borne pathogens is a key issue that needs to be addressed. Infection with an arthropod-borne flavivirus is known to induce oxidative stress in insect cells. We hypothesize that vector-derived Prxs could have an effect on the infection and/or replication of flaviviruses in the hosts, since ticks Prxs are possibly transmitted from ticks to their hosts. In this study, we established stable strains of baby hamster kidney (BHK) cells expressing two types of H2O2-scavenging Prxs from the hard tick Haemaphysalis longicornis (BHK-HlPrx and BHK-HlPrx2 cells). Although the infection of TBEV surrogate Langat virus (LGTV) did not induce H2O2 production in normal BHK cells, the mortality rate and the virus titer of LGTV infected BHK-HlPrx cells increased. In addition, HlPrx proteins in BHK cells can facilitate LGTV replication in cells, while HlPrx2 proteins in BHK cells cannot. The results also demonstrated that this facilitation of LGTV replication by the 1-Cys Prx in the BHK cells is not by scavenging H2O2 but by an unknown mechanism. In order to understand this mechanism, more studies using tick-derived cells and ticks are necessary.